Older Adults' Behavioral Intentions Toward Advance Care Planning Based on Theory of Reasoned Action. Issue 6 (26th December 2022) - Ke, Li-Shan; Cheng, Hui-Chuan; Ku, Yu-Chen; Lee, Ming-Ju; Chang, Su-Yu; Huang, Hsiu-Ying; Lin, Yin-Ling
Abstract : This study aimed to explore the factors affecting the behavioral intentions of older adults toward advance care planning (ACP). A questionnaire survey was conducted at 2 medical wards and a senior activity center in northern Taiwan. Four hundred one participants were older adults aged over 65 years, comprising hospitalized patients, their caregivers, and members of a senior activity center. The regression model revealed that participant type (patient, caregiver, or community resident); financial support; discussion of ACP with family; and knowledge, attitudes, and subjective norms accounted for 46.3% of the variance in behavioral intentions. The behavioral intention of caregivers was higher than that of patients. The behavioral intention of participants who were financially dependent on the family was lower than that of pensioners. Regarding discussing ACP with family, older adults in the contemplation and preparation stages score higher on behavioral intention than those in the precontemplation stage. This study supports the theory of reasoned action. Older adults' ACP knowledge and attitudes need to be enhanced through education. Caregivers' behavioral intentions tend to perform ACP. Sharing their caring experiences may be a strategy for promoting ACP. Older adults' financial status affects their behavioral intentions. Therefore, financial planning should be performed early and should incorporate ACP.